Anti-fingerprint beauty glue

By fluoricizing the nano -nanotoxic, nanoccal carbonate, and micron -level sea bubble stones, and scattered in beauty glue, a rough structure of microfimal scale is formed to solve the problem of being easily stained with fingerprints after beauty glue curing. Jia's anti -fingerprint performance.

CN119119949BActive Publication Date: 2025-01-28SHANDONG YONGAN ADHESIVE IND
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411608612.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-28
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Existing beauty glues are prone to fingerprints after curing, which affects the aesthetic effect and is troublesome to deal with. There is also a lack of products on the market that can completely avoid fingerprint pollution.

Method used

By fluoride the surface of nano -nanocarbing, nano -calcium carbonate, and microned sea bubble stones, the surface has the performance of hydrophobic oil and oil, and through the high -speed dispersing process of dual -planet mixer, these fillers are evenly dispersed into beauty glue. Form the rough structure of a graded micr -nanometer -scale to improve the hydrophobic and oil sparseness of the glue layer.

Benefits of technology

The excellent anti -fingerprint performance of the surface after curing the beauty glue is achieved, reducing the adhesion of water and oil pollution, and improving the ionizing force sliding from the surface, making it difficult for beauty glue to contain fingerprints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an anti-fingerprint beauty glue, belonging to the technical field of adhesives. The specific formula of the anti-fingerprint beauty glue is, by weight: 120-160 parts of α,ω-dihydroxy polydimethylsiloxane, 16-33 parts of dimethyl silicone oil, 10-20 parts of polytrifluoropropyl methylsiloxane, 0.5-2.5 parts of fluorine-modified nano-silicon dioxide, 10-35 parts of fluorine-modified nano-calcium carbonate, 15-40 parts of fluorine-modified micron-sized sepiolite, 0.3-1.3 parts of catalyst, and 6-11 parts of cross-linking agent. The anti-fingerprint beauty glue obtained by the invention has a surface drying time of 13-14 minutes, an adhesive strength of 1.87-2.11 MPa, a tensile strength of 2.26-2.58 MPa, an elastic recovery rate of 96-98%, a Shore hardness of 59-62, a water contact angle of 169-175°, an oil contact angle of 154-160°, a flame retardant grade of V0, and no fingerprint traces when the surface is pressed 10 times with a finger.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an anti-fingerprint beauty glue, belonging to the technical field of adhesives. Background Art

[0002] Beauty glue used for interior decoration, also known as silicone glue or silicone sealant, is widely used for sealing and beautifying edges of windows, countertops, cabinets, wardrobes, closets, wooden doors, mirrors, skirtings, ceilings, wall tiles and other parts. With the continuous enrichment of beauty glue product types and people's diversified requirements for home decoration color, personalization and easy care, consumers continue to put forward various functional requirements for beauty glue, among which the anti-fingerprint performance is of high concern. After the beauty glue is cured, human fingers are easily contaminated by fingerprints after contacting the surface, affecting the lasting aesthetic effect, and it is more troublesome to take care of. There is water and skin oil on the surface of human fingers. The most fundamental reason why the beauty glue is easily contaminated with fingerprints after curing is that the hydrophobic and oleophobic properties of the beauty glue surface are relatively poor. However, there are almost no beauty glues on the market that can completely achieve fingerprint-free performance. Therefore, the development of beauty glue with excellent hydrophobic and oleophobic properties is very in line with the actual needs of the market.

[0003] Chinese patent CN105754512A discloses a matte anti-fingerprint, anti-scratch conductive cloth single-sided tape and a preparation method. The anti-fingerprint performance of the patented tape surface is obtained by adding an anti-fingerprint solution to form a surface coating. The anti-fingerprint solution is composed of a fluorinated polymer and heptadecafluorotriethoxysilane in a mass ratio of 1:1. However, this anti-fingerprint solution needs to be heated and dried to form a scratch-resistant and anti-fingerprint cured adhesive layer. The added drying method is not suitable for beauty adhesives that are dried and cured at room temperature.

[0004] Chinese patent CN112143394A discloses an anti-fingerprint tape for wireless chargers, including a black ink layer, a substrate layer and an adhesive layer. The patent adds polyethyleneimine and octadecyldimethylbenzyl ammonium chloride to waterborne polyurethane, carbon black and 1,1',1"-methylenetri(4-isocyanate)benzene to make the tape have anti-fingerprint properties. The hydrophobic and oleophobic properties of polyethyleneimine and octadecyldimethylbenzyl ammonium chloride are not particularly good, so the anti-fingerprint tape obtained by the patent has limited resistance to fingerprint pollution, and polyethyleneimine and octadecyldimethylbenzyl ammonium chloride are not suitable for silicone system beauty glue.

[0005] From the above, we can see that there is little research on anti-fingerprint beauty glue in the adhesive industry. Therefore, developing an anti-fingerprint beauty glue suitable for home decoration is of great practical significance to fill the market gap. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides an anti-fingerprint beauty glue to achieve the following invention objectives: to prepare an anti-fingerprint beauty glue with excellent hydrophobic and oleophobic properties.

[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0008] An anti-fingerprint beauty glue, the specific formula of the anti-fingerprint beauty glue is, in parts by weight:

[0009] 120-160 parts of α,ω-dihydroxy polydimethylsiloxane,

[0010] 16-33 parts of dimethyl silicone oil,

[0011] 10-20 parts of polytrifluoropropylmethylsiloxane,

[0012] 0.5~2.5 parts of fluorine-modified nano-silicon dioxide,

[0013] 10~35 parts of fluorine-modified nano calcium carbonate,

[0014] 15-40 parts of fluorine-modified micron-sized sepiolite,

[0015] Catalyst 0.3~1.3 parts,

[0016] 6-11 parts of cross-linking agent;

[0017] The polytrifluoropropylmethylsiloxane has a molecular weight of 300-1300 g / mol, a hydroxyl mass content of 1-7 wt %, a viscosity of 30-130 mPa·s at 25° C., and a fluorine content of 10-25 wt %.

[0018] The catalyst is dibutyltin dilaurate;

[0019] The cross-linking agent is one of methyltrimethoxysilane and methyltriethoxysilane;

[0020] The following are further improvements to the above technical solution:

[0021] Step 1: Preparation of fluorine-modified nano-silica

[0022] The nano-silicon dioxide powder is dried at 100-130° C. for 5-9 hours, cooled to room temperature, added to a high-speed dispersion kettle, and then toluene and sodium tridecyl sulfosuccinate are added. After strong dispersion at a speed of 9000-13000 rpm for 3-6 hours, the dispersion rate is reduced to 1500-3500 rpm, the temperature is increased and kept constant at 95-125° C., hexamethyldisilazane is then added, and the reaction is carried out at a constant temperature for 3-6 hours under condensation reflux, and then 2-perfluorooctylethanol is added, and the reaction is continued at a constant temperature for 4-8 hours under condensation reflux, and then the temperature is reduced to room temperature, the material is centrifuged, and the solid obtained by centrifugation is washed with anhydrous ethanol for 3-5 times, and vacuum dried at 50-80° C. for 4-9 hours to obtain fluorine-modified nano-silicon dioxide;

[0023] The particle size of the nano silicon dioxide powder is 10-50 nm;

[0024] The mass ratio of the nano silicon dioxide powder, toluene, sodium tridecyl sulfosuccinate, hexamethyldisilazane and 2-perfluorooctylethanol is 15-40:140-200:1-3:2-8:4-12.

[0025] Step 2: Preparation of fluorine-modified nano-calcium carbonate

[0026] Fluoroamine and xylene are added to a reaction kettle, and the stirring rate is controlled at 400-700 rpm, and the temperature is raised and kept constant at 80-110°C, and then 3-isocyanate propyl trimethoxy silane is added. After the reaction is stirred at a constant temperature for 5-9 hours under condensation reflux, a fluorine-containing siloxane active solution is obtained. Then, the nano calcium carbonate powder is dried at 100-140°C for 4-7 hours, and after cooling to room temperature, it is added to a high-speed dispersion kettle, and then p-xylene and methyl palmitate are added. After strong dispersion at a speed of 8000-11000 rpm for 4-9 hours, the dispersion rate is reduced to 2500-4500 rpm, and the temperature is raised and kept constant at 75-105°C, and then the fluorine-containing siloxane active solution is added. After the reaction is kept constant at condensation reflux for 5-9 hours, the temperature is reduced to room temperature, and the material is centrifuged. The solid obtained by centrifugation is washed with anhydrous ethanol for 3-5 times, and vacuum dried at 60-85°C for 3-7 hours to obtain fluorine-modified nano calcium carbonate;

[0027] The fluoroamine is one of 2,2,2-trifluoroethylamine and 4,4,4-trifluorobutylamine;

[0028] In the fluorinated siloxane active solution, the mass ratio of fluoroamine, xylene and 3-isocyanate propyltrimethoxysilane is 10-45:60-120:6-20;

[0029] The mass ratio of the nano-calcium carbonate powder, xylene, methyl palmitate, and fluorinated silicone active solution is 20-40:45-100:2-6:40-90;

[0030] The particle size of the nano calcium carbonate powder is 10-80 nm.

[0031] Step 3: Preparation of fluorine-modified micron-sized sepiolite

[0032] After drying the micron-sized sepiolite at 100-130°C for 4-8 hours, cooling to room temperature, adding the micron-sized sepiolite to a reactor, adding toluene and butyl phosphate, controlling the stirring rate at 1500-2500 rpm, raising the temperature and maintaining the temperature at 85-110°C, stirring and dispersing for 6-10 hours under condensation reflux, reducing the stirring rate to 700-1000 rpm, then adding fluorine-containing silane, continuing to stir and react under condensation reflux for 7-12 hours, filtering, washing the filtered solid with anhydrous ethanol for 3-5 times, and drying at 80-95°C for 4-7 hours to obtain fluorine-modified micron-sized sepiolite;

[0033] The fluorine-containing silane is one of 1,2-bis(methyldifluorosilyl)ethane and nonafluorohexyltri(dimethylamino)silane;

[0034] The mass ratio of the micron-sized sepiolite, toluene, butyl phosphate and fluorinated silane is 25-50:160-330:2-8:6-15;

[0035] The particle size of the micron-sized sepiolite is 1-3.5 μm.

[0036] Step 4: Preparation of anti-fingerprint beauty glue

[0037] According to the specific formula of the anti-fingerprint beauty glue in parts by weight, α,ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, polytrifluoropropyl methylsiloxane, a catalyst and a cross-linking agent are put into a double planetary mixer that has been dried and evacuated in advance, and the vacuum negative pressure of the double planetary mixer is maintained at -0.09~-0.08MPa. Under the conditions of controlling the stirring rate at 80~110 rpm and the dispersion rate at 6000~8000 rpm, after stirring and dispersing for 60~100 minutes, the stirring rate is increased to 120~150 rpm and the dispersion rate is increased to 9000~11000 rpm, and then fluorine-modified nano-silicon dioxide and fluorine-modified nano-calcium carbonate are added, and the stirring and dispersion is continued for 6~10 hours, and then fluorine-modified micron-sized sepiolite is added, and the stirring and dispersion is continued for 8~12 hours to obtain a glue solution, which is allowed to stand and continuously evacuate and degas, and then filled into a plastic finished product bottle, and sealed with nitrogen to obtain a finished anti-fingerprint beauty glue product.

[0038] Compared with the prior art, the present invention achieves the following beneficial effects:

[0039] 1. The present invention performs surface fluorine modification on two nano-scale fillers, nano-silicon dioxide and nano-calcium carbonate, and performs surface fluorine modification on the micron-scale sepiolite, so that the surfaces of the three filler particles have hydrophobic and oleophobic properties. Then, the high-speed dispersion process of the double planetary mixer is used to evenly disperse the three surface fluorine-modified fillers into the beauty glue mainly composed of α, ω-dihydroxy polydimethylsiloxane. After the glue is cured, the surface fluorine-modified nano-scale fillers and the surface fluorine-modified micro-scale fillers will form a graded micro-nano-scale rough structure on the surface of the cured glue layer. This micro-nano- The graded rough structure increases the contact angle between the adhesive layer surface and water and oil stains, and also reduces the rolling angle between the adhesive layer surface and water and oil stains. Thus, while reducing the adhesion between the adhesive layer surface and water and oil stains, it increases the release force of water and oil stains sliding off the adhesive layer surface (i.e., the interfacial adhesion between water and oil stains and the adhesive layer surface). Therefore, the adhesive layer surface of the beauty glue after curing is difficult to be stained with water and oil stains from the finger surface, because the adhesion between water and oil stains and the finger surface is much greater than the adhesion between water and oil stains and the adhesive layer surface. Therefore, the beauty glue obtained by the present invention has extremely excellent anti-fingerprint performance;

[0040] 2. The present invention uses hexamethyldisilazane, which has a very high hydroxyl reactivity, to first perform a hydrophobic treatment on the surface of nano-silica. The surface of the nano-silica covered with hexamethyldisilazane has nitrogen-hydrogen bonds and silicon-hydrogen bonds with high reactivity. These two chemical bonds are easy to continue to react with 2-perfluorooctylethanol containing active hydroxyl groups. Therefore, after the surface of the nano-silica is covered with hydrophobic hexamethyldisilazane, it is also covered with 2-perfluorooctylethanol, which has particularly good oleophobicity. Therefore, the fluorine-modified nano-silica has hydrophobic and oleophobic properties. After being evenly dispersed in the formula of the beauty glue, it can bring excellent hydrophobic and oleophobic properties to the surface of the cured beauty glue layer.

[0041] 3. The present invention utilizes the hydrogen bonding between 2,2,2-trifluoroethylamine, 4,4,4-trifluorobutylamine and the hydroxyl groups on the surface of nano-calcium carbonate. 2,2,2-trifluoroethylamine or 4,4,4-trifluorobutylamine forms a coating layer on the surface of nano-calcium carbonate, and then 3-isocyanate propyltrimethoxysilane reacts with the two fluoroamine substances in the coating layer to form a chemically bonded stable coating layer. The surface of the coating layer is a carbon-fluorine non-polar covalent bond. Therefore, the surface of the nano-calcium carbonate changes from a strong polarity to a hydrophobic and oleophobic double surface. After being added into the formula of the beauty glue, it plays a key role in improving the hydrophobic and oleophobic properties of the beauty glue.

[0042] 4. The present invention uses 1,2-bis(methyldifluorosilyl)ethane or nonafluorohexyltri(dimethylamino)silane, two fluorine-containing silanes with high reaction activity, to fluorinate the micron-sized sepiolite with rich hydroxyl functional groups on the surface. The fluorinated micron-sized sepiolite has hydrophobic and oleophobic properties on the surface. After being uniformly dispersed in the formula of the beauty glue, the micron-sized sepiolite with the oleophobic properties forms a micro-nano secondary rough structure with the fluorine-modified nano-sized filler, thereby making the beauty glue have excellent anti-fingerprint performance;

[0043] 5. The anti-fingerprint beauty glue obtained by the present invention has a surface drying time of 13-14 minutes, an adhesive strength of 1.87-2.11 MPa, a tensile strength of 2.26-2.58 MPa, an elastic recovery rate of 96-98%, a Shore hardness of 59-62, a water contact angle of 169-175°, an oil contact angle of 154-160°, a flame retardant grade of V0, and no fingerprint marks are left on the surface after being pressed 10 times with a finger. DETAILED DESCRIPTION

[0044] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0045] Embodiment 1: An anti-fingerprint beauty glue

[0046] Step 1: Preparation of fluorine-modified nano-silica

[0047] The nano-silicon dioxide powder is dried at 120° C. for 6 hours, cooled to room temperature and added to a high-speed dispersion kettle, then toluene and sodium ditridecyl sulfosuccinate are added, and after strong dispersion at a speed of 12,000 rpm for 5 hours, the dispersion rate is reduced to 2,500 rpm, the temperature is increased and kept constant at 105° C., hexamethyldisilazane is then added, and the reaction is carried out at a constant temperature for 4 hours under condensation reflux, and then 2-perfluorooctylethanol is added, and the reaction is continued at a constant temperature for 5 hours under condensation reflux, and then the reaction is cooled to room temperature, the material is centrifuged, and the solid obtained by centrifugation is washed 4 times with anhydrous ethanol, and vacuum dried at 60° C. for 6 hours to obtain fluorine-modified nano-silicon dioxide;

[0048] The particle size of the nano silicon dioxide powder is 40 nm;

[0049] The mass ratio of the nano silicon dioxide powder, toluene, sodium tridecyl sulfosuccinate, hexamethyldisilazane and 2-perfluorooctylethanol is 35:180:2:5:9.

[0050] Step 2: Preparation of fluorine-modified nano-calcium carbonate

[0051] Fluoroamine and xylene were added to a reaction kettle, and the stirring rate was controlled at 600 rpm, and the temperature was raised and kept constant at 95°C, and then 3-isocyanate propyl trimethoxy silane was added. After the reaction was stirred at a constant temperature for 8 hours under condensation reflux, a fluorine-containing siloxane active solution was obtained. Then the nano calcium carbonate powder was dried at 130°C for 6 hours, and added to a high-speed dispersion kettle after cooling to room temperature. Then p-xylene and methyl palmitate were added, and after strong dispersion at a speed of 9000 rpm for 8 hours, the dispersion rate was reduced to 4000 rpm, and the temperature was raised and kept constant at 95°C, and then the fluorine-containing siloxane active solution was added. After the reaction was kept constant at condensation reflux for 8 hours, the temperature was reduced to room temperature, and the material was centrifuged. The solid obtained by centrifugation was washed with anhydrous ethanol for 4 times, and vacuum dried at 80°C for 6 hours to obtain fluorine-modified nano calcium carbonate;

[0052] The fluoroamine is 2,2,2-trifluoroethylamine;

[0053] In the fluorinated siloxane active solution, the mass ratio of fluoroamine, xylene and 3-isocyanate propyltrimethoxysilane is 35:80:15;

[0054] The mass ratio of the nano calcium carbonate powder, xylene, methyl palmitate, and fluorinated silicone active solution is 35:60:5:80;

[0055] The particle size of the nano calcium carbonate powder is 30 nm.

[0056] Step 3: Preparation of fluorine-modified micron-sized sepiolite

[0057] After drying the micron-sized sepiolite at 120° C. for 5 hours, cooling it to room temperature, adding the micron-sized sepiolite to a reactor, adding toluene and butyl phosphate, raising the temperature to 100° C. and maintaining the temperature under a stirring rate of 1800 rpm, stirring and dispersing it under a condensation reflux state for 9 hours, reducing the stirring rate to 900 rpm, then adding fluorine-containing silane, continuing to stir and react under a condensation reflux state for 10 hours, filtering, washing the filtered solid with anhydrous ethanol for 4 times, and drying it at 90° C. for 5 hours to obtain fluorine-modified micron-sized sepiolite;

[0058] The fluorine-containing silane is 1,2-bis(methyldifluorosilyl)ethane;

[0059] The mass ratio of the micron-sized sepiolite, toluene, butyl phosphate and fluorinated silane is 45:250:5:11;

[0060] The particle size of the micron-sized sepiolite is 2.5 μm.

[0061] Step 4: Preparation of anti-fingerprint beauty glue

[0062] The specific formula of the anti-fingerprint beauty glue is, by weight:

[0063] 150 parts of α,ω-dihydroxy polydimethylsiloxane,

[0064] 26 parts of dimethyl silicone oil,

[0065] 17 parts of polytrifluoropropylmethylsiloxane,

[0066] 2 parts of fluorine-modified nano-silica,

[0067] 25 parts of fluorine-modified nano calcium carbonate,

[0068] 30 parts of fluorine-modified micron-sized sepiolite,

[0069] 1 part of catalyst,

[0070] 9 parts of cross-linking agent;

[0071] The polytrifluoropropylmethylsiloxane has a molecular weight of 700 g / mol, a hydroxyl mass content of 4 wt%, a viscosity of 100 mPa·s at 25° C., and a fluorine content of 18 wt%;

[0072] The catalyst is dibutyltin dilaurate;

[0073] The cross-linking agent is methyltrimethoxysilane;

[0074] According to the specific formula of the anti-fingerprint beauty glue in parts by weight, α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, polytrifluoropropyl methylsiloxane, a catalyst, and a cross-linking agent are placed in a double planetary mixer that has been dried and evacuated in advance, and the vacuum negative pressure of the double planetary mixer is maintained at -0.088MPa. The stirring rate is controlled at 90 rpm and the dispersion rate is controlled at 6500 rpm. After stirring and dispersing for 90 minutes, the stirring rate is increased to 140 rpm and the dispersion rate is increased to 9500 rpm. Then, fluorine-modified nano-silicon dioxide and fluorine-modified nano-calcium carbonate are added. After continuous stirring and dispersing for 9 hours, fluorine-modified micron-sized sepiolite is added. After continuous stirring and dispersing for 11 hours, a glue solution is obtained. After standing and continuous vacuuming and degassing, the glue solution is filled into a plastic finished product bottle, and sealed with nitrogen to obtain a finished anti-fingerprint beauty glue product.

[0075] Embodiment 2: An anti-fingerprint beauty glue

[0076] Step 1: Preparation of fluorine-modified nano-silica

[0077] The nano-silica powder is dried at 100° C. for 5 hours, cooled to room temperature and added to a high-speed dispersion kettle, then toluene and sodium tridecyl sulfosuccinate are added, and after strong dispersion at a speed of 9000 rpm for 3 hours, the dispersion rate is reduced to 1500 rpm, the temperature is increased and kept constant at 95° C., hexamethyldisilazane is then added, and the reaction is continued at a constant temperature under condensation reflux for 3 hours, and then 2-perfluorooctylethanol is added, and the reaction is continued at a constant temperature under condensation reflux for 4 hours, and then the temperature is reduced to room temperature, the material is centrifuged, and the solid obtained by centrifugation is washed 3 times with anhydrous ethanol, and vacuum dried at 50° C. for 4 hours to obtain fluorine-modified nano-silica;

[0078] The particle size of the nano silicon dioxide powder is 10 nm;

[0079] The feeding mass ratio of the nano silicon dioxide powder, toluene, sodium tridecyl sulfosuccinate, hexamethyldisilazane and 2-perfluorooctylethanol is 15:140:1:2:4.

[0080] Step 2: Preparation of fluorine-modified nano-calcium carbonate

[0081] Fluoroamine and xylene were added to a reaction kettle, and the stirring rate was controlled at 400 rpm, and the temperature was raised and kept constant at 80°C, and then 3-isocyanate propyl trimethoxysilane was added, and the reaction was stirred at a constant temperature for 5 hours under condensation reflux to obtain a fluorine-containing siloxane active solution, and then the nano calcium carbonate powder was dried at 100°C for 4 hours, and added to a high-speed dispersion kettle after cooling to room temperature, and then p-xylene and methyl palmitate were added, and after strong dispersion at a speed of 8000 rpm for 4 hours, the dispersion rate was reduced to 2500 rpm, and the temperature was raised and kept constant at 75°C, and then the fluorine-containing siloxane active solution was added, and the reaction was kept constant at condensation reflux for 5 hours, and then the temperature was reduced to room temperature, and the material was centrifuged, and the solid obtained by centrifugation was washed 3 times with anhydrous ethanol, and vacuum dried at 60°C for 3 hours to obtain fluorine-modified nano calcium carbonate;

[0082] The fluoroamine is 4,4,4-trifluorobutylamine;

[0083] In the fluorinated siloxane active solution, the mass ratio of fluoroamine, xylene and 3-isocyanate propyltrimethoxysilane is 10:60:6;

[0084] The mass ratio of the nano calcium carbonate powder, xylene, methyl palmitate, and fluorinated silicone active solution is 20:45:2:40;

[0085] The particle size of the nano calcium carbonate powder is 10 nm.

[0086] Step 3: Preparation of fluorine-modified micron-sized sepiolite

[0087] After drying the micron-sized sepiolite at 100° C. for 4 hours, the mixture was cooled to room temperature, added to a reaction kettle, and then toluene and butyl phosphate were added. The mixture was heated to 85° C. and kept at a constant temperature under a stirring rate of 1500 rpm. After stirring and dispersing the mixture under condensation reflux for 6 hours, the stirring rate was reduced to 700 rpm, and then fluorine-containing silane was added. The mixture was stirred and reacted under condensation reflux for 7 hours, and then filtered. The filtered solid was washed with anhydrous ethanol for 3 times, and then dried at 80° C. for 4 hours to obtain fluorine-modified micron-sized sepiolite.

[0088] The fluorine-containing silane is nonafluorohexyltris(dimethylamino)silane;

[0089] The mass ratio of the micron-sized sepiolite, toluene, butyl phosphate and fluorinated silane is 25:160:2:6;

[0090] The particle size of the micron-sized sepiolite is 1 μm.

[0091] Step 4: Preparation of anti-fingerprint beauty glue

[0092] The specific formula of the anti-fingerprint beauty glue is, by weight:

[0093] 120 parts of α,ω-dihydroxy polydimethylsiloxane,

[0094] 16 parts of dimethyl silicone oil,

[0095] 10 parts of polytrifluoropropylmethylsiloxane,

[0096] 0.5 parts of fluorine-modified nano-silicon dioxide,

[0097] 10 parts of fluorine-modified nano calcium carbonate,

[0098] 15 parts of fluorine-modified micron-sized sepiolite,

[0099] 0.3 parts of catalyst,

[0100] 6 parts of cross-linking agent;

[0101] The polytrifluoropropylmethylsiloxane has a molecular weight of 300 g / mol, a hydroxyl mass content of 1 wt%, a viscosity of 30 mPa·s at 25°C, and a fluorine content of 10 wt%;

[0102] The catalyst is dibutyltin dilaurate;

[0103] The cross-linking agent is methyltriethoxysilane;

[0104] According to the specific formula of the anti-fingerprint beauty glue in parts by weight, α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, polytrifluoropropyl methylsiloxane, a catalyst and a cross-linking agent are put into a double planetary mixer that has been dried and evacuated in advance, and the vacuum negative pressure of the double planetary mixer is maintained at -0.09 MPa. The stirring rate is controlled at 80 rpm and the dispersion rate is 6000 rpm. After stirring and dispersing for 60 minutes, the stirring rate is increased to 120 rpm and the dispersion rate is increased to 9000 rpm, and then fluorine-modified nano-silicon dioxide and fluorine-modified nano-calcium carbonate are added. After continuous stirring and dispersing for 6 hours, fluorine-modified micron-sized sepiolite is added, and stirring and dispersing is continued for 8 hours to obtain a glue solution. After standing and continuous vacuuming and degassing, the glue solution is filled into a plastic finished product bottle, and sealed with nitrogen to obtain a finished anti-fingerprint beauty glue product.

[0105] Embodiment 3: An anti-fingerprint beauty glue

[0106] Step 1: Preparation of fluorine-modified nano-silica

[0107] The nano-silicon dioxide powder is dried at 130° C. for 9 hours, cooled to room temperature and added to a high-speed dispersion kettle, then toluene and sodium ditridecyl sulfosuccinate are added, and after strong dispersion at a speed of 13,000 rpm for 6 hours, the dispersion rate is reduced to 3,500 rpm, the temperature is increased and kept constant at 125° C., hexamethyldisilazane is then added, and the reaction is carried out at a constant temperature under condensation reflux for 6 hours, and then 2-perfluorooctylethanol is added, and the reaction is continued at a constant temperature under condensation reflux for 8 hours, and then the reaction is cooled to room temperature, the material is centrifuged, and the solid obtained by centrifugation is washed with anhydrous ethanol for 5 times, and vacuum dried at 80° C. for 9 hours to obtain fluorine-modified nano-silicon dioxide;

[0108] The particle size of the nano silicon dioxide powder is 50nm;

[0109] The feeding mass ratio of the nano silicon dioxide powder, toluene, sodium tridecyl sulfosuccinate, hexamethyldisilazane and 2-perfluorooctylethanol is 40:200:3:8:12.

[0110] Step 2: Preparation of fluorine-modified nano-calcium carbonate

[0111] Fluoroamine and xylene were added to a reaction kettle, and the stirring rate was controlled at 700 rpm, and the temperature was raised and kept constant at 110°C, and then 3-isocyanate propyl trimethoxysilane was added. After the reaction was stirred at a constant temperature for 9 hours under condensation reflux, a fluorine-containing siloxane active solution was obtained. Then the nano calcium carbonate powder was dried at 140°C for 7 hours, and added to a high-speed dispersion kettle after cooling to room temperature. Then p-xylene and methyl palmitate were added, and after strong dispersion at a speed of 11000 rpm for 9 hours, the dispersion rate was reduced to 4500 rpm, and the temperature was raised and kept constant at 105°C, and then the fluorine-containing siloxane active solution was added. After the reaction was kept constant at condensation reflux for 9 hours, the temperature was reduced to room temperature, and the material was centrifuged. The solid obtained by centrifugation was washed with anhydrous ethanol for 5 times, and vacuum dried at 85°C for 7 hours to obtain fluorine-modified nano calcium carbonate.

[0112] The fluoroamine is 2,2,2-trifluoroethylamine;

[0113] In the fluorinated siloxane active solution, the mass ratio of fluoroamine, xylene and 3-isocyanatepropyltrimethoxysilane is 45:120:20;

[0114] The mass ratio of the nano calcium carbonate powder, xylene, methyl palmitate, and fluorinated silicone active solution is 40:100:6:90;

[0115] The particle size of the nano calcium carbonate powder is 80 nm.

[0116] Step 3: Preparation of fluorine-modified micron-sized sepiolite

[0117] After drying the micron-sized sepiolite at 130° C. for 8 hours, the micron-sized sepiolite was cooled to room temperature, added to a reaction kettle, and then toluene and butyl phosphate were added. The stirring rate was controlled at 2500 rpm, and the temperature was raised and kept constant at 110° C. After stirring and dispersing for 10 hours under condensation reflux, the stirring rate was reduced to 1000 rpm, and then fluorine-containing silane was added. The reaction was continued under condensation reflux with stirring for 12 hours, and then filtered. The filtered solid was washed with anhydrous ethanol for 5 times, and dried at 95° C. for 7 hours to obtain fluorine-modified micron-sized sepiolite.

[0118] The fluorine-containing silane is 1,2-bis(methyldifluorosilyl)ethane;

[0119] The mass ratio of the micron-sized sepiolite, toluene, butyl phosphate and fluorinated silane is 50:330:8:15;

[0120] The particle size of the micron-sized sepiolite is 3.5 μm.

[0121] Step 4: Preparation of anti-fingerprint beauty glue

[0122] The specific formula of the anti-fingerprint beauty glue is, by weight:

[0123] 160 parts of α,ω-dihydroxy polydimethylsiloxane,

[0124] 33 parts of dimethyl silicone oil,

[0125] 20 parts of polytrifluoropropylmethylsiloxane,

[0126] 2.5 parts of fluorine-modified nano-silicon dioxide,

[0127] 35 parts of fluorine-modified nano calcium carbonate,

[0128] 40 parts of fluorine-modified micron-sized sepiolite,

[0129] 1.3 parts of catalyst,

[0130] 11 parts of cross-linking agent;

[0131] The polytrifluoropropylmethylsiloxane has a molecular weight of 1300 g / mol, a hydroxyl mass content of 7 wt %, a viscosity of 130 mPa·s at 25° C., and a fluorine content of 25 wt %.

[0132] The catalyst is dibutyltin dilaurate;

[0133] The cross-linking agent is one of methyltrimethoxysilane and methyltriethoxysilane;

[0134] According to the specific formula of the anti-fingerprint beauty glue in parts by weight, α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, polytrifluoropropyl methylsiloxane, a catalyst and a cross-linking agent are put into a double planetary mixer that has been dried and evacuated in advance, and the vacuum negative pressure of the double planetary mixer is maintained at -0.08MPa. Under the conditions of controlling the stirring rate at 110 rpm and the dispersion rate at 8000 rpm, after stirring and dispersing for 100 minutes, the stirring rate is increased to 150 rpm and the dispersion rate is increased to 11000 rpm, and then fluorine-modified nano-silicon dioxide and fluorine-modified nano-calcium carbonate are added. After continuous stirring and dispersing for 10 hours, fluorine-modified micron-sized sepiolite is added, and stirring and dispersing is continued for 12 hours to obtain a glue solution. After standing and continuous vacuuming and degassing, the glue solution is filled into a plastic finished product bottle, and sealed with nitrogen to obtain a finished anti-fingerprint beauty glue product.

[0135] Comparative Example 1: Based on Example 1, step 1, preparation of fluorine-modified nano-silicon dioxide and step 2, preparation of fluorine-modified nano-calcium carbonate are not performed. In step 4, preparation of anti-fingerprint beauty glue, 2 parts of fluorine-modified nano-silicon dioxide and 25 parts of fluorine-modified nano-calcium carbonate are replaced by 27 parts of fluorine-modified micron-sized sepiolite in equal amounts. The specific operation is as follows:

[0136] Step 1, preparation of modified zirconium phosphate and step 2, preparation of fluorine-modified nano-calcium carbonate are not performed;

[0137] The operation of step 3 is the same as that of embodiment 1;

[0138] Step 4: Preparation of anti-fingerprint beauty glue

[0139] 2 parts of fluorine-modified nano-silicon dioxide and 25 parts of fluorine-modified nano-calcium carbonate were replaced by 27 parts of fluorine-modified micron-sized sepiolite in equal amounts, and the other operations were the same as in Example 1.

[0140] Comparative Example 2: Based on Example 1, step 3, preparation of fluorine-modified micron-sized sepiolite, is not performed. In step 4, preparation of anti-fingerprint beauty glue, 30 parts of fluorine-modified micron-sized sepiolite are replaced by 30 parts of fluorine-modified nano-calcium carbonate. The specific operation is as follows:

[0141] The operations of steps 1 and 2 are the same as those of Example 1;

[0142] Step 3, preparation of fluorine-modified micron-sized sepiolite, is not performed;

[0143] Step 4: Preparation of anti-fingerprint beauty glue

[0144] 30 parts of fluorine-modified micron-sized sepiolite were replaced by 30 parts of fluorine-modified nano-calcium carbonate, and the other operations were the same as in Example 1.

[0145] Comparative Example 3: Based on Example 1, step 1, preparation of fluorine-modified nano-silica, is not performed. In step 4, preparation of anti-fingerprint beauty glue, 2 parts of fluorine-modified nano-silica are replaced by 2 parts of nano-silica. The specific operation is as follows:

[0146] Step 1, preparation of fluorine-modified nano-silica is not performed;

[0147] The operations of steps 2 and 3 are the same as those of Example 1;

[0148] Step 4: Preparation of anti-fingerprint beauty glue

[0149] The 2 parts of fluorine-modified nano-silica were replaced by 2 parts of nano-silica in equal amounts, and the other operations were the same as in Example 1.

[0150] Comparative Example 4: Based on Example 1, step 2, preparation of fluorine-modified nano-calcium carbonate, is not performed. In step 4, preparation of anti-fingerprint beauty glue, 25 parts of fluorine-modified nano-calcium carbonate are replaced by 25 parts of nano-calcium carbonate. The specific operation is as follows:

[0151] The operation of step 1 is the same as that of embodiment 1;

[0152] Step 2, preparation of fluorine-modified nano-calcium carbonate, is not performed;

[0153] The operation of step 3 is the same as that of embodiment 1;

[0154] Step 4: Preparation of anti-fingerprint beauty glue

[0155] 25 parts of fluorine-modified nano-calcium carbonate were replaced by 25 parts of nano-calcium carbonate, and the other operations were the same as in Example 1.

[0156] Performance Test:

[0157] The anti-fingerprint beauty glue obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4 was subjected to the following performance tests:

[0158] 1. Surface drying time: Tested in accordance with GB / T13477.3-2017;

[0159] 2. Adhesion performance: Tested in accordance with GB / T 11211-2009;

[0160] 3. Tensile strength: Tested in accordance with GB / T528-2009;

[0161] 4. Elastic recovery rate: Tested in accordance with GB / T13477.17-2002;

[0162] 5. Shore hardness: Tested in accordance with GB / T531.1-2008;

[0163] 6. Hydrophobic and oleophobic properties: The hydrophobic and oleophobic properties of the surface of the cured adhesive layer were tested using a DSA100 contact angle meter from Krueger GmbH, Germany. Water and edible oil were used as hydrophobic and oleophobic probe liquids, and the droplets were discharged through a micro-syringe with a drop volume of 4 μL / drop. The droplet equilibrium time was based on the contact angle reading being basically unchanged. The average value of 5 times was taken for each sample.

[0164] 7. Anti-fingerprint test: Press the surface of the glue layer after the beauty glue is cured with your finger 10 times to observe whether there are fingerprints on the surface of the glue layer;

[0165] The specific test results are shown in Table 1:

[0166] Table 1

[0167]

[0168] From the data in Table 1, it can be seen that in Comparative Example 1, no fluorine-modified nano-silicon dioxide and fluorine-modified nano-calcium carbonate are added, and only fluorine-modified micron-sized sepiolite is added. Compared with Example 1, the surface drying time of Comparative Example 1 is significantly increased, the three mechanical performance indicators of bonding strength, tensile strength, and elastic recovery rate are greatly reduced, and the Shore hardness is increased. This shows that if only micron-sized sepiolite is added without nano-sized fillers, the mechanical properties of the beauty glue are difficult to be effectively improved. In addition to the mechanical properties, the water contact angle and oil contact angle of Comparative Example 1 are significantly reduced, and the anti-fingerprint performance is lost. This shows that only adding micron-sized fluorine-modified fillers will increase the surface of the glue layer. The hydrophobic and oleophobic properties are difficult to be improved to the greatest extent; the way of adding fillers in Comparative Example 2 is exactly opposite to that in Comparative Example 1, no fluorine-modified micron-sized sepiolite is added, and only fluorine-modified nano-silicon dioxide and fluorine-modified nano-calcium carbonate are added. Compared with Example 1, the surface drying time of Comparative Example 2 does not change, the bonding strength, tensile strength, and elastic recovery rate are slightly reduced, and the Shore hardness does not change significantly, which shows that not adding fluorine-modified micron-sized sepiolite has no significant effect on the curing process of the beauty glue and the mechanical properties after curing, but the water contact angle and oil contact angle of Comparative Example 2 are significantly reduced, and the reduction is greater than that of Comparative Example 1, and there is no anti-fingerprint performance. This shows that it is difficult to obtain a surface with particularly good hydrophobic and oleophobic properties by only adding nano-scale fluorine-modified fillers; in Comparative Example 3, the added nano-silica is not fluorine-modified, and the surface drying time of Comparative Example 3 is slowed down to 20 minutes, the bonding strength, tensile strength, and elastic recovery rate are sharply reduced, and the Shore hardness increases. This is because the nano-silica is not fluorine-modified, and it is difficult to obtain nano-scale dispersion in the beauty glue formula, which will then lead to a significant decrease in various mechanical properties after the colloid is cured due to agglomeration. In addition, the water contact angle and oil contact angle of Comparative Example 3 are significantly reduced, and the hydrophobic and oleophobic functions are lost. This may be due to the hydrophilic nano-silica After agglomeration, a very small hydrophilic area is formed on the surface of the cured adhesive layer; the nano calcium carbonate added in Comparative Example 4 is not fluorine-modified, and the situation is similar to that in Comparative Example 3, and the degree of extension of the surface drying time and the decrease in the bonding strength, tensile strength, and elastic recovery rate are much greater than those in Comparative Example 3. The water contact angle and the oil contact angle also drop to the lowest values ​​among all the embodiments and comparative examples, and the hydrophobic and oleophobic properties are reduced to the worst. This may be due to the relatively large amount of nano calcium carbonate added. Without surface fluorine modification, it is difficult to be effectively dispersed in the beauty glue formula. The serious agglomeration between the nano calcium carbonate powder particles leads to a sharp decline in various properties.

[0169] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An anti-fingerprint beauty glue, characterized in that: The specific formula of the anti-fingerprint beauty glue is, by weight: 120-160 parts of α,ω-dihydroxy polydimethylsiloxane, 16-33 parts of dimethyl silicone oil, 10-20 parts of polytrifluoropropylmethylsiloxane, 0.5~2.5 parts of fluorine-modified nano-silicon dioxide, 10~35 parts of fluorine-modified nano calcium carbonate, 15-40 parts of fluorine-modified micron-sized sepiolite, Catalyst 0.3~1.3 parts, 6-11 parts of cross-linking agent; The polytrifluoropropylmethylsiloxane has a molecular weight of 300-1300 g / mol, a hydroxyl mass content of 1-7 wt %, a viscosity of 30-130 mPa·s at 25° C., and a fluorine content of 10-25 wt %. The catalyst is dibutyltin dilaurate; The cross-linking agent is one of methyltrimethoxysilane and methyltriethoxysilane; The fluorine-modified nano-silica has a preparation method comprising: drying the nano-silica powder at 100-130°C for 5-9 hours, cooling to room temperature and adding the powder to a high-speed dispersion kettle, then adding toluene and sodium ditridecyl sulfosuccinate, strongly dispersing the powder at a speed of 9000-13000 rpm for 3-6 hours, reducing the dispersion rate to 1500-3500 rpm, raising the temperature and maintaining the temperature at 95-125°C, then adding hexamethyldisilazane, carrying out a constant temperature reaction at a condensation reflux state for 3-6 hours, then adding 2-perfluorooctylethanol, continuing to carry out a constant temperature reaction at a condensation reflux state for 4-8 hours, then cooling the powder to room temperature, centrifuging the powder, washing the solid obtained by centrifugation with anhydrous ethanol for 3-5 times, and vacuum drying the solid at 50-80°C for 4-9 hours to obtain the fluorine-modified nano-silica. The fluorine-modified nano calcium carbonate is prepared by adding fluoroamine and xylene into a reaction kettle, controlling the stirring rate to 400-700 rpm, raising the temperature and maintaining the temperature at 80-110° C., and then adding 3-isocyanate propyltrimethoxysilane. After reacting at a constant temperature and stirring for 5 to 9 hours under condensation reflux, a fluorinated silicone active solution is obtained, and then the nano calcium carbonate powder is dried at 100 to 140° C. for 4 to 7 hours, and added to a high-speed dispersion kettle after cooling to room temperature, and then p-xylene and methyl palmitate are added, and after strong dispersion at a speed of 8000 to 11000 rpm for 4 to 9 hours, the dispersion rate is reduced to 2500 to 4500 rpm, and the temperature is increased and kept constant at 75 to 105° C., and then the fluorinated silicone active solution is added, and the reaction is continued at a constant temperature for 5 to 9 hours under condensation reflux, and then the temperature is reduced to room temperature, and the material is centrifuged, and the solid obtained by centrifugation is washed with anhydrous ethanol for 3 to 5 times, and then vacuum dried at 60 to 85° C. for 3 to 7 hours to obtain fluorine-modified nano calcium carbonate; The fluoroamine is one of 2,2,2-trifluoroethylamine and 4,4,4-trifluorobutylamine; The fluorine-modified micron-sized sepiolite is prepared by: drying the micron-sized sepiolite at 100-130°C for 4-8 hours, cooling to room temperature, adding the micron-sized sepiolite to a reaction kettle, adding toluene and butyl phosphate, controlling the stirring rate at 1500-2500 rpm, raising the temperature to 85-110°C and maintaining the temperature constant, stirring and dispersing for 6-10 hours under a condensation reflux state, reducing the stirring rate to 700-1000 rpm, then adding fluorine-containing silane, continuing to stir and react under a condensation reflux state for 7-12 hours, filtering, washing the filtered solid with anhydrous ethanol for 3-5 times, and drying at 80-95°C for 4-7 hours to obtain the fluorine-modified micron-sized sepiolite; The fluorine-containing silane is one of 1,2-bis(methyldifluorosilyl)ethane and nonafluorohexyltri(dimethylamino)silane.

2. The anti-fingerprint beauty glue according to claim 1, characterized in that: The particle size of the nano silicon dioxide powder is 10-50 nm; The mass ratio of the nano silicon dioxide powder, toluene, sodium tridecyl sulfosuccinate, hexamethyldisilazane and 2-perfluorooctylethanol is 15-40:140-200:1-3:2-8:4-12.

3. The anti-fingerprint beauty glue according to claim 1, characterized in that: In the fluorinated siloxane active solution, the mass ratio of fluoroamine, xylene and 3-isocyanate propyltrimethoxysilane is 10-45:60-120:6-20; The mass ratio of the nano-calcium carbonate powder, xylene, methyl palmitate, and fluorinated silicone active solution is 20-40:45-100:2-6:40-90; The particle size of the nano calcium carbonate powder is 10-80 nm.

4. The anti-fingerprint cosmetic adhesive according to claim 1, characterized in that: The mass ratio of the micron-sized sepiolite, toluene, butyl phosphate and fluorinated silane is 25-50:160-330:2-8:6-15; The particle size of the micron-sized sepiolite is 1-3.5 μm.

5. The anti-fingerprint cosmetic adhesive according to claim 1, characterized in that: The preparation method of the anti-fingerprint beauty glue is as follows: according to the specific formula of the anti-fingerprint beauty glue in parts by weight, α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, polytrifluoropropyl methylsiloxane, a catalyst, and a cross-linking agent are placed in a double planetary mixer that has been dried and evacuated in advance, the vacuum negative pressure of the double planetary mixer is maintained at -0.09 to -0.08 MPa, the stirring rate is controlled at 80 to 110 rpm and the dispersion rate is 6000 to 8000 rpm, and the mixture is stirred. After stirring and dispersing for 60 to 100 minutes, the stirring rate is increased to 120 to 150 rpm and the dispersion rate is increased to 9000 to 11000 rpm, and then fluorine-modified nano-silicon dioxide and fluorine-modified nano-calcium carbonate are added, and stirring and dispersing is continued for 6 to 10 hours. Then, fluorine-modified micron-sized sepiolite is added, and stirring and dispersing is continued for 8 to 12 hours to obtain a glue solution. After standing and continuous vacuum degassing, it is filled into a plastic finished product bottle, and sealed with nitrogen to obtain an anti-fingerprint beauty glue product.

Citation Information

Patent Citations

  • Non-bright, anti-fingerprint and scraping-resistant single-side adhesive tape for conductive fabric and preparation method

    CN105754512A

  • Anti-fingerprint adhesive tape for wireless charger

    CN112143394A

  • Nanopowder hydrophobicity and lipophobicity modification method

    CN106893391A

  • Preparation method of modified meerschaum / polyurethane super-hydrophobic / super-oleophobic coating

    CN110922875A